Training on Adjusting the Format Template for Writing Scientific Articles and How to Submit Them in Order to Improve the Quality of Student Scientific Work: Pelatihan Penyesuaian Template Format Penulisan Artikel Ilmiah Serta Cara Submitnya Dalam Rangka Meningkatkan Kualitas Karya Ilmiah Mahasiswa - Khamo, Khamo Waruwu; Elyani, Elyani; Cindy , Cindy Yolanda; Ulfa, Ulfa Utari; Ayunda , Ayunda Fatmasari; Oppie, Oppie Meisya Tanjung (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
At this time students are required to be better able to develop themselves in writing scientific papers and publications. The results of scientific work are not only limited to graduation requirements but are the ability of these students to continue to develop and produce scientific works that are made systematically and structured in answering problems that occur in society. In order to help students self-development to publish their scientific works, our community service team conducts training for younger students who have passed the court hearing to be able to write their scientific work into scientific journals and submit them for publication. This activity is carried out in the form of training and hands-on practice. This training was conducted for students who graduated from the Faculty of Islamic Religion, majoring in Islamic Communication and Broadcasting. This training is only limited to 10 students and 3 accompanying lecturers, considering that we are still obliged to maintain health protocols in this new normal. The results of this training show that most students are able to understand and practice directly the stages of converting a thesis into a journal article according to the template and submitting scientific work to a predetermined journal.